(untitled) (London Journal of Research In Science: Natural and Formal, 2025)
We will attempt to summarize in this text the private scientific research that our team has conducted on rotational dynamics over the past forty years. The document analyses the rotation and orbiting of rigid solid bodies, and specifically of celestial bodies, arriving at a Theory of Dynamic Interactions (TDI) as a solution to the problems not resolved by Keplers and Newtons laws, by taking into account the simultaneous orbital and rotational movements of planets. The text describes experiments that demonstrate how a body in rotation and translation can alter its trajectory, thus challenging the classical Newtonian model. The TDI explains the behaviours of bodies that simultaneously orbit and rotate, and it can be applied to dynamic phenomena that meet those conditions, such as the case of boomerang flight, gyroscopes, or the anomalies observed in the Pioneer probes, offering a new interpretation of these behaviours. The text suggests that this theory provides new insights into understanding rotational dynamics and the harmony of the universe, proposing a defined mathematical model for modern physics and for certain natural phenomena.